Sex differences in left ventricular function and beta-receptor responsiveness following prolonged strenuous exercise - Scott, Jessica M; Esch, Ben T A; Haykowsky, Mark J; Isserow, Saul; Koehle, Michael S; Hughes, Bevan G; Zbogar, Dominik; Bredin, Shannon S D; McKenzie, Don C; Warburton, Darren E R (Journal of applied physiology (1985), 2007)
Sex differences in neuroendocrine and metabolic responses to prolonged strenuous exercise (PSE) have been well documented. The aim of this investigation was to examine sex differences in left ventricular function and cardiac beta-receptor responsiveness following a single bout of PSE. Nine male and eight female triathletes were examined during three separate sessions: before, immediately after, and 24 h following a half-ironman triathlon using dobutamine stress echocardiography. Steady-state graded infusions of dobutamine were used to assess beta-receptor responsiveness. Slopes calculated from linear regressions between dobutamine doses and changes in heart rate and contractility for each participant were used as an index of beta-receptor responsiveness. Despite no change in preload, fractional area change decreased from baseline after the race in both men and women, with a greater decrease in men [men: 54.1% (SD 2.1) to 50.7% (SD 3.4) vs. women: 55.4% (SD 2.7) to 53.3% (SD 2.5); P < 0.05]. The amount of dobutamine necessary to increase heart rate by 25 beats/min [men: 29.6 microg x kg(-1) x min(-1) (SD 6.6) to 42.7 microg x kg(-1) x min(-1) (SD 12.9) vs. women: 23.5 microg x kg(-1) x min(-1) (SD 4.0) to 30.0 microg x kg(-1) x min(-1) (SD 7.8); P < 0.05] and contractility by 10 mmHg/cm2 [men: 20.9 microg x kg(-1) x min(-1) (SD 5.1) to 37.0 microg x kg(-1) x min(-1) (SD 11.5) vs. women: 22.6 microg x kg(-1) x min(-1) (SD 6.4) to 30.7 microg x kg(-1) x min(-1) (SD 7.2); P < 0.05] was greater in both men and women postrace. However, the amount of dobutamine required to induce these changes was greater in men, reflecting larger beta-receptor alterations in male triathletes following PSE relative to women. These data suggest that following an acute bout of PSE, male triathletes demonstrate an attenuated chronotropic and inotropic response to beta-adrenergic stimulation compared with female triathletes.